커피 찌꺼기를 이용한 Methylene Blue 염료 흡착특성 연구 - 강슬기; 박진희; 김동수 (한국수처리학회지, 28(2), 2020)
In this study, coffee ground as waste resources were recycled to remove methylene blue dye wastewater by the adsorption treatment. It was investigated that the adsorption mechanism of methylene blue on the coffee ground based on the isotherm, kinetics and thermodynamics using the various experiment factor like pH, ionic strength and temperature. As coffee ground dosage increased, the adsorption efficiency increased from 26.2% to 94.1%. On the contrary, the unit adsorption amount decreased as coffee ground dosage increased. The maximum unit adsorption amount was 16.33 mg/g when coffee ground dosage was 20 mg. The adsorption efficiency was shown to be over 90% in the pH range of 4 to 11. Below pH 4, adsorption efficiency was significantly decreased. The adsorption process followed Langmuir isotherm equation well, and the value of RL demonstrated that the adsorption process is suitable. The kinetic parameters also indicated that the adsorption followed pseudo second equation better than pseudo first equation. The thermodynamic parameters ΔG°, ΔH° and ΔS° values calculated to be the adsorption belonged to the physical adsorption process, and it was advantageous at low temperature. As the result, it was confirmed that the adsorption study of methylene blue using coffee ground was the exothermic reaction and adsorption freedom decreased. KCI Citation Count: 0